Research on Musical Mood Portrayal of Yilatu’s "Second Morin Khuur Concerto" from the Perspective of Integration of Nationality and Modernity - Hu, Manda (Education Insights, 2026)
In contemporary Chinese instrumental composition, the integration of ethnic musical traditions with modern compositional techniques has become an important creative approach for expanding expressive possibilities while preserving cultural identity. As a representative traditional instrument of the Mongolian people, the morin khuur possesses distinctive timbral qualities and rich cultural connotations, making it a significant medium for such exploration. Yilatu’s Second Morin Khuur Concerto exemplifies this trend by combining modern musical language with elements derived from Mongolian musical traditions. Rather than depicting a concrete narrative or programmatic scene, the concerto constructs an expressive musical trajectory through the contrast and transformation of musical moods. This study divides the work into three sections corresponding to the expressive states of dilemma, struggle, and victory, and analyzes how these moods are articulated through changes in melody, harmony, tonality, rhythm, and texture. The opening section employs atonal writing and dissonant harmonic structures, particularly tritone-based sonorities, to convey tension and instability; the middle section introduces modal melodies influenced by Mongolian folk music and repetitive structural techniques to express awakening consciousness and resistance; and the final section establishes a clear tonal framework and consonant harmonic texture to symbolize resolution and victory. Through detailed musical analysis, this paper demonstrates how tonal contrast functions as a core expressive mechanism in the concerto, offering interpretative insights for performers and contributing to the study of contemporary morin khuur composition within the broader context of ethnic instrumental modernization.